Association of symmetrical alkane diols with pyridine DFT/GIAO calculation of 1 H NMR chemical shifts - Lomas, John S (Magnetic resonance in chemistry : MRC, 2016)
Copyright © 2016 John Wiley & Sons, Ltd.